The roles of leadership, organisational culture and information technology as mediating factor in knowledge management at Malaysian public universities - Hasannuddiin Hassan (2022)
Knowledge management is challenging and crucial in institutions of higher learning. However, comprehensive research in the public universities setting is relatively limited. The purpose of this thesis is to examine the importance of knowledge management from the perspectives of leadership, organisational culture, and information management. Data were collected from top management and senate members at all Malaysian Public Universities using the qualitative and quantitative research method. For the qualitative method, data were collected through face-to-face interviews with five vice-chancellors, and the data was then analysed using ATLAS.ti. Samples were selected by utilising judgmental sampling. For the quantitative method, the data was collected using selfadministered questionnaires from 285 senate members and further analysed using SPSS both for descriptive statistics to describe the demographic profiles of the respondents and Structural Equation Modelling using AMOS for inferential statistics. In the quantitative study, samples were selected using simple random sampling with the sample size determined based on Krejcie and Morgan (1970). The analyses are meant to provide evidence to answer all research questions and serve as a basis to support the hypotheses. Based on the findings, all dimensions tested in the study are indicated as having a strong relationship with knowledge management. As for the findings from the quantitative study, results have indicated the same direction as the qualitative data, whereby all dimensions have revealed a positive, strong relationship with knowledge management. Thus, the findings have supported all the hypotheses tested in the study. Consequently, it is suggested that the institutions of higher learning factors are leadership, organizational culture, and information technology in enhancing knowledge management and sustaining good knowledge management practice. More importantly, people should make full use of information and communication technology to manage, mediate, make decisions, and share information.